Ngugi's novels and African history : narrating the nation - Ogude, James (Pluto Press, 1999)
Ngugi wa Thiong'o is one of Africa's most controversial and renowned literary figures. This comprehensive study explores the relationship between history and narrative in his novels.
Keywords: Ngũgĩ wa Thiongʼo, -- 1938- -- Knowledge -- History.; Ngũgĩ wa Thiongʼo, -- 1938- -- Fictional works.; Ngũgĩ wa Thiongʼo, -- 1938-; Historical fiction, Kenyan (English) -- History and criticism.; Literature and history -- Africa -- History -- 20th century.; Literature and history -- Kenya -- History -- 20th century.; Littérature et histoire -- Afrique -- Histoire -- 20e siècle.; Littérature et histoire -- Kenya -- Histoire -- 20e siècle.; LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh.; HISTORY -- Africa -- General.; History; Criticism and interpretation; Historical fiction, Kenyan (English); Literature and history; Africa; Kenya; Romans.; 1900-1999; Criticism, interpretation, etc.